Effect of Ivermectin against Psoroptic mange in rabbits - Sivajothi, S; Reddy, B.Sudhakara; Rayulu, V.C. (International Journal of Scientific World, 2014)
The present report is on Psoroptic mange infestation in rabbits. Out of 126 rabbits in a farm 34 were infested. Observed clinical signs were alopecia, crusts formation, superficial and deep skin fissures and itching. Distribution of lesions was noticed around the base of ears, margins of the ears and face. Skin scrapings from infested rabbits were examined and eggs, larvae, nymphs and adult mites were recovered. The infected rabbits were treated with ivermectin @ 200µg/kg body weight first day subcutaneously followed by orally once in 48 hours along with antibiotic and supportive therapy. Improvement in the condition was noticed after 4th day of therapy. Keywords: Psoriatic mange, Rabbits, Ivermectin.